(untitled) (World Bulletin of Management and Law, 2023)
Infringement of the private life of the family constitutes a violation of the constitution which guaranteed her protection first, and a clear violation of the laws second, which required the guarantee of protection from infringement of her privacy, and gave her the right to file a lawsuit before the judiciary demanding compensation for the damages suffered as a result of these violations, so that she may demand the lifting of the damage represented by the removal of the infringement in addition to seeking monetary compensation it is the infringement for which the family can seek compensation that falls on any member of the family if he or she is challenged with his honour offer or reputation so that the family as a whole is affected. The judiciary should not tolerate the imposition of compensation on the aggressor because of the goal of reparation, and the preservation of the privacy of the family from the encroachment of others, because it has an impact on the preservation of society, because the family is the basis of society.